REFORMASI HUKUM PIDANA KEKERASAN SEKSUAL DARI KUHP KE KEADILAN KORBAN - Elfa, Elfa Murdiana; Murdiana, Elfa; Mufti Rayhan, Alendra Nauval (Jurnal Supremasi, 2025)
This article examines the transformation of Indonesia’s criminal justice approach to sexual violence, shifting from retributive justice in the Criminal Code (KUHP) toward substantive justice that prioritizes victim protection through Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). The core issue lies in fragmented regulations, narrow legal definitions, and limited support mechanisms for victims. Employing a normative legal method with statutory, conceptual, and theoretical approaches, this study explores the paradigm shift in criminal law. Findings indicate that UU TPKS reflects principles of responsive law, progressive legal thought, and victim-oriented legal politics through holistic mechanisms for protection and recovery. However, gaps in implementation persist due to institutional limitations and entrenched legal formalism. Recommendations include regulatory harmonization, trauma-informed training for law enforcement, and strengthened recovery infrastructure to ensure that substantive justice for victims is meaningfully realized.